1980
DOI: 10.1002/micr.1920010513
|View full text |Cite
|
Sign up to set email alerts
|

The hazard of cigarette smoking following digital replantation

Abstract: Two case histories are presented in which cigarette smoking in the early postoperative period following digital replantation led to vasospasm and thus compromise of the microvascular anastomoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…A recent paper by Harris et al [8] reported on the possible hazard of cigarette smoking after microvascular surgery. Two similar cases of postoperative arterial insufficiency attributable to smoking after microvascular surgery have been seen in our unit.…”
mentioning
confidence: 98%
“…A recent paper by Harris et al [8] reported on the possible hazard of cigarette smoking after microvascular surgery. Two similar cases of postoperative arterial insufficiency attributable to smoking after microvascular surgery have been seen in our unit.…”
mentioning
confidence: 98%
“….). That much said, less widely publicized findings show that delayed wound healing directly related to tobacco consumption in reconstructive surgery following excision of a tumor, in cosmetic surgery and in upper limb trauma is 20 to 50% more prevalent in smokers than in non-smokers [4,6,8,26].…”
Section: Discussionmentioning
confidence: 99%
“…These pathophysiological effects have been observed during clinical practice, particularly in would healing [3], abdominoplasty [4], breast reconstruction [5], digital replantation [6], face lifting [7,8] and breast reduction [9]. In free tissue transfer operations, tobacco accounts for an increased morbidity of donor sites at considerable social cost [10].…”
Section: Introductionmentioning
confidence: 99%
“…Zwei andere Studien konnten deutlich machen, dass das Rauchen von Zigaretten in der frühen postoperativen Phase zu einem Gefäßspasmus führt, der die Anastomosenheilung bedroht [20,22]. Alle Studien zusammen stimmen darin überein, dass Patienten nach einer Replantation das Rauchen untersagt werden sollte, um eine optimale Zirkulation zu garantieren.…”
Section: Replantationunclassified